Examining China’s public health discourse on juvenile myopia issues: a multimodal critical discourse analysis on a public health promotion advertisement - Lyu, Tianxiong (Frontiers in Public Health, 2025)
This article analyses a public health promotion advertisement on juvenile myopia issues, which stands out as one of the most widely viewed among those addressing juvenile myopia prevention released by the National Health Commission of the People’s Republic of China (NHC) on bilibili, a prominent video-sharing platform in China. The article discusses how a designed public health discourse on juvenile myopia issues is constructed through various techniques and what ideologies can be reflected through this discourse. Employing a multimodal critical discourse analysis (MCDA) approach based on the three-dimensional discourse framework, this article underscores how the advertisement intricately employs diverse semiotic resources to craft its discursive script. Notably, through designed narrative genres, characters, scenes, and settings, the ad strategically amplifies the role of adult parents as pivotal agents in preventing juvenile myopia, thus legitimizing their primary responsibility. However, this emphasis on parental responsibility subtly obscures the influence exerted by other societal actors and social factors in the myopia prevention landscape. Through this nuanced analysis, the study sheds light on the attempt of public policy discourse hidden in the advertisement to shape perceptions and attitudes toward myopia prevention, underscoring its underlying intention to advance the tenets of neoliberal biopedagogy.